Consumer Behavior of Starbucks Coffee Shops in Bangkok - et. al., Nattapong Tamkaew, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to study the consumer’s demographic characteristics that affect the consumers' use of Starbucks coffee shops in Bangkok, to study the marketing ingredient factors affecting the coffee shop usage of Starbucks for consumers in Bangkok and to study the factors of marketing mix that affect the consumer loyalty in Starbucks coffee shops in Bangkok. This research surveyed 405 consumers in Bangkok area. The tools used for data collection were the statistical questionnaire to analyze the data, namely frequency, percentage, mean (x̄) and standard deviation (S.D). The results of this study showed that Starbucks coffee shop usage behavior of consumers in Bangkok area can be determine the behavior of consumers' purchase intentions which coffee shops should be considered brand value in recognition of service quality and trust in what is probably to be a key factor in making a purchase decision in order that it can be used in a Starbucks coffee shop. The direction that customers can trust and purchase their products including find those operate in all sales channels that applied the service quality and brand value to suit their business. In Accordance with customers' purchasing intentions in Bangkok and Starbucks coffee shops, they can be applied to develop appropriate marketing strategies such as creating more socially responsible activities including the development of personnel for service quality that is superior to competitors.